Коловратки (Rotatoria) жаберной полости длиннопалого речного рака бассейна Днепра. Сообщение I - Бошко, Е.Г. (Вестник зоологии, 1980)
Rotifers of the Lepadella genus (L. astacicola, L. lata, L. branchicola, L. raja, L. nаnа) and the Dicranophorus genus (D. hauerianus) specific for crawfish are found in the gill cavity of Astacus (Pontastacus) leptodactilus E s c h s c h o l t z from the Dnieper basin. Original redescriptions and drawings are presented for species from the Lepadella ge nus Lepadella nаnа, a new for science species, and L. lata var. ovata, a new variety of the species, are described.